Ethnic Spatial Dispersion and Immigrant Identity - Amelie F. Constant; Simone Schüller; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2013)
Ethnic groups tend to agglomerate and assemble, mostly in urban areas. While ethnic clustering is critically debated in societies and the consequences for economic outcomes are under debate in research, the process is not yet well understood. A separate literature has also examined the cultural and ethnic identity of immigrants and how these affect their economic performance and societal integration. However, an unexplored channel connects ethnic clustering with ethnic identity formation. Therefore this paper examines the role of ethnic geographic clustering in the sociocultural integration of immigrants. It employs survey data from the German Socio-Economic Panel, combined with disaggregated information at a low geographical level from the unexploited German full census of 1970 and 1987. We employ the exogenous placement of immigrants during their recruitment in the 1960s and 1970s and find that local co-ethnic concentration affects immigrants' cultural integration. Residential ethnic clustering strengthens immigrants' retention of an affiliation with their respective country of origin and weakens identification with the host society. The effects are nonlinear and only become significant at relatively high levels of co-ethnic concentration for the minority identity and at very low levels of local concentration for the majority identity. Our findings are robust to the use of an instrumental variable approach.
Keywords: J15; R23; Z10; 330; ethnic minorities; residential segregation; ethnic identity; spatial dispersion; ethnic enclaves